A method for soluble overexpression of the α7 nicotinic acetylcholine receptor extracellular domain - Fischer, Markus (The National Academy of Sciences, 2001)
We describe the construction of a soluble protein carrying the N-terminal extracellular domain (ECD) of the α7 subunit of the nicotinic acetylcholine receptor. The approach was to fuse the α7 ECD at the C and N termini of several monomeric and pentameric soluble carrier proteins and to investigate the soluble expression of the product in Escherichia coli. An initial screening of six carrier proteins resulted in the selection of a fusion protein comprising, from the N to the C terminus, the maltose binding protein, a 17-aa linker containing an enterokinase binding site, and the α7 ECD. This protein is soluble upon expression in bacteria and is purified by affinity chromatography. It binds the competitive nicotinic antagonist α-bungarotoxin with 2.5 μM affinity and displays a CD spectrum corresponding to a folded protein. The method might be suitable to produce large quantities of protein for crystallization and immunochemical experiments.